2022
DOI: 10.3390/ijerph19116517
|View full text |Cite
|
Sign up to set email alerts
|

Trends of the Prevalence of Pre-gestational Diabetes in 2030 and 2050 in Belgrade Cohort

Abstract: The aim of this study was to analyze the trends in diabetes in pregnancy in Belgrade, Serbia for the period of the past decade and forecast the number of women with pre-gestational diabetes for the years 2030 and 2050. The study included the data on all pregnant women with diabetes from the registry of the deliveries in Belgrade, by the City Institute of Public Health of Belgrade, Serbia for the period between 2010 and 2020 and the published data on the deliveries on the territory of Belgrade. During the exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Naglašava se značaj potencijalnog razvoja dijabetesa u kasnijem životnom dobu jer je aktuelan trend povećavanja njegove prevalence kod odraslih osoba, samim tim i kod žena, zbog potencijalne trudnoće opterećene ovim komorbiditetom. Prevalenca pregestacionog dijabetesa kod trudnica povećala se u prethodnoj deceniji u Beogradu, i očekuje se njen dalji porast, kao i to da će se duplirati do 2050. godine [23].…”
Section: Sklonost Ka Metaboličkim Poremećajimaunclassified
See 1 more Smart Citation
“…Naglašava se značaj potencijalnog razvoja dijabetesa u kasnijem životnom dobu jer je aktuelan trend povećavanja njegove prevalence kod odraslih osoba, samim tim i kod žena, zbog potencijalne trudnoće opterećene ovim komorbiditetom. Prevalenca pregestacionog dijabetesa kod trudnica povećala se u prethodnoj deceniji u Beogradu, i očekuje se njen dalji porast, kao i to da će se duplirati do 2050. godine [23].…”
Section: Sklonost Ka Metaboličkim Poremećajimaunclassified
“…Oni su ispitivali senzitivnost na insulin i sekreciju insulina u vezi sa veličinom tela na rođenju kod muškaraca i tial pregnancy burdened by this comorbidity. The prevalence of pregestational diabetes in pregnant women has increased in the past decade in Belgrade and it is expected to continue rising, and even to double by 2050 [23]. Also, it has been shown that women with type 1 diabetes have an increased risk of pregnancy complications and unfavorable neonatal outcomes compared to those with type 2 diabetes or gestational diabetes mellitus [24].…”
Section: Tendency To Metabolic Syndromementioning
confidence: 99%
“…2 With the increasing prevalence of obesity and lifestyle changes, the prevalence of GDM has also significantly increased two to three times in approximately 10 years. 3 In recent years, with the lowering of the diagnostic threshold for GDM, the regulation of diet and exercise, and the strengthening of fetal monitoring, fetal complications caused by GDM have been properly managed. However, maternal complications, such as gestational hypertension and preeclampsia (PE), have not received enough attention.…”
Section: Introductionmentioning
confidence: 99%